2014
DOI: 10.3389/fpsyt.2014.00179
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Role of Social Cognition in Major Depressive Disorder

Abstract: Background: Social cognition – the ability to identify, perceive, and interpret socially relevant information – is an important skill that plays a significant role in successful interpersonal functioning. Social cognitive performance is recognized to be impaired in several psychiatric conditions, but the relationship with major depressive disorder is less well understood. The aim of this review is to characterize the current understanding of: (i) the different domains of social cognition and a possible relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
181
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(203 citation statements)
references
References 52 publications
14
181
2
6
Order By: Relevance
“…This method usually includes tasks in which participants view short video vignettes depicting interactions between actors, and are asked to answer a set of questions regarding these interactions to which there is a correct or incorrect response (e.g., the Awareness of Social Inference Test; McDonald, Flanagan, Rollins, & Kinch, 2003). Studies using this type of tasks have usually found individuals with clinical depression to have impaired MSAS functioning (e.g., Ladegaard et al, 2014;Wolkenstein et al, 2011; for a review see Schreiter et al, 2013;Weightman et al, 2014). The same has been found for individuals with elevated depressive symptoms (e.g., Ambady & Gray, 2002).…”
Section: Depression and The Msasmentioning
confidence: 89%
See 1 more Smart Citation
“…This method usually includes tasks in which participants view short video vignettes depicting interactions between actors, and are asked to answer a set of questions regarding these interactions to which there is a correct or incorrect response (e.g., the Awareness of Social Inference Test; McDonald, Flanagan, Rollins, & Kinch, 2003). Studies using this type of tasks have usually found individuals with clinical depression to have impaired MSAS functioning (e.g., Ladegaard et al, 2014;Wolkenstein et al, 2011; for a review see Schreiter et al, 2013;Weightman et al, 2014). The same has been found for individuals with elevated depressive symptoms (e.g., Ambady & Gray, 2002).…”
Section: Depression and The Msasmentioning
confidence: 89%
“…In contrast to the large number of studies of depression and the ESS, only few have focused on depression and the MSAS (Ladegaard, Larsen, Videbech, & Lysaker, 2014;Weightman, Air, & Baune, 2014). Like the ESS, MSAS functioning has been assessed in several ways.…”
Section: Depression and The Msasmentioning
confidence: 98%
“…The ability to infer emotional mental states of others appears then to be linked with the effective use of emotions for appropriate personal judgment in decision-making with possible consequence in social wellbeing. Further, an altered ability to correctly interpret emotional states might be responsible of difficulties with social interaction, as observed in major depressive disorder [35], and this issue deserves to be explored in future studies. Finally, it might be object of future studies to evaluate potential benefit of a rehabilitative approach combining motor, cognitive and social training paradigms in FOG.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of depression can alter the course of RA negatively via cognitive-behavioural or inflammatory pathways: patients with concurrent depression suffer from more pain, show a heightened disease activity (Rathbun et al, 2013) as well as generally poorer health outcomes (Morris et al, 2011). Some specific characteristics of people suffering from depression, such as negatively biased (social) cognitions or motivational deficits, can affect behaviours and the way in which cognitions shape behaviours (Weightman et al, 2014;Wisco and NolenHoeksema, 2010). This suggests consequences for adherence behaviours: DiMatteo et al (2000) analysed the relationship between depression and adherence to various treatment regimes and found depression to contribute to medication non-adherence among patients with different medical conditions.…”
mentioning
confidence: 99%